Editorial: The strenghts and weaknesses of thinking - Pasierbek, Wit (Horyzonty Wychowania, 2009)
Thinking is the fundamental function of human mind. The process of thinking takes place in the brain and consists in associations, using memory, using certain store of information and on this basis formulating conclusions, which not infrequently may turn out to be illusory or false. Reflection and dialogue are connected with the process of thinking too. Some people believe that man’s intelligence is a measure of thinking. We also differentiate certain mental categories such as: positive and negative, creative, strategic, inductive, deductive, abstract, logical and many more. These categories depend on the subject which “processes” the mind in the process of thinking as well as their usefulness. It is Descartes himself who at the beginning of the 17th century in the famous statement: cogito ergo sum (I think, therefore I am) attributes the fundamental function to this human ability, since it is directly connected with his consciousness and being.